تعليم اللغة العربيّة باستخدام طريقة الإستجابة الجسدية الكاملة (Total Physical Response) في مركز تطوير اللغة (PPB) بجامعة أنتساري الإسلامية الحكومية بنجرماسين - أنصار, محمد كامل رمّا (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
Abstract: Total Physical Response method in language teaching is a method that aims to determine students' understanding through verbal instruction. Therefore, a teacher needs a method that allows for student fun learn with indepedently and also that can build chemistry between teachers and students. This research Used Classroom Action that consists of four steps: planning, acting, observation and reflection. Subject of this research was students studying in first semester in Center of Developing language at UIN Antasari university in academic year 2018-2019. Result of research indicate that applying of physical response method proven effectively about the improving of Arabic language skill of student in first level. Therefore, it is very important for the language teachers to pay attention of this method in Arabic learning process and also these findings had implications for the importance of academic policy affirmations from leader university for the development of strategies and methodologies of learning Arabic skills.